Influence of stacking fault energy in electrically assisted uniaxial tension of FCC metals. Issue 3 (11th February 2017) - Breda, M.; Calliari, I.; Bruschi, S.; Forzan, M.; Ghiotti, A.; Michieletto, F.; Spezzapria, M.; Gennari, C.
Abstract : Electrically assisted manufacturing is based on the electro-plastic effect induced by electricity on the material flow during deformation and represents an alternative method for forming materials. Several studies have pointed out the real effectiveness of this technique, but no relations among microstructure, electrical resistivity, crystal structure and deformation-mode have been revealed. In the present work, the stacking fault energy (SFE) was taken into account and three FCC materials possessing different SFEs were strained in electrically assisted uniaxial tension under continuous current application. The results showed an advantageous electric contribution only in the highest SFE material, whereas no enhancements in formability were revealed in the investigated low- and intermediate-SFE metals.